THE TECHNIQUES OF TEACHING VOCABULARY ASPECT TO ELEMENTARY LEVEL LEARNERS - Abdurashidova Bumayram Kamoliddin qizi; Qoʻchqorova Zulfizar Abduhamidovna (Лучшие интеллектуальные исследования, 2023)
Abstract: This article based on the use of strategies, activities and games on teaching vocabulary for young learners.